What are the consumer welfare effects of tariff increases in South Africa? - Mambara, Simbarashe Tinotenda (School of Economics, 2026)
This paper investigates how tariffs affect domestic prices of chicken and, through this, household welfare in South Africa. Our choice of chicken was motivated by its importance as a source of protein and the several trade measures applied against chicken meat. We conducted our analysis in two stages. In the first stage, we focused on price transmission, specifically how a change in trade policy affects domestic prices, by estimating the passthrough of chicken duties at a spatial level. We used disaggregated pricing data at the retail level across the entire country. In the second stage, we focused on welfare effects and used micro-level household survey data. Therefore, the welfare impacts depended on the magnitude of pass-through estimated in the first stage. The findings in the first stage showed a high tariff pass-through across provinces, ranging from 0.533 to 0.786. Additionally, we found urban pass-through to be higher than rural pass-through in most of the provinces. In the second stage, we found that the changes in domestic prices of chicken induced by chicken duties were highly regressive and affected poorer and rural households. For example, higher chicken prices caused total household expenditure to increase by 0.3% to 7% across provinces and expenditure decile. Our results can be explained not only in relation to the different incomes of the households, but also by the diverse effects on spatial prices that have resulted from increase in chicken duties.